2020 IEEE Haptics Symposium (HAPTICS) 2020
DOI: 10.1109/haptics45997.2020.ras.hap20.156.6c3cc0bf
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effectiveness of Haptic Alarm Displays for Critical Care Environments

Abstract: A thesis submitted to McGill University in partial fulfillment of the requirements for the degree of Master of Engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 57 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…However, an advantage for such displays seems to have been found by Burdick et al (2019). In recent work, Alirezaee et al (2020) demonstrated that nonclinician participants could detect heart rate (HR), blood pressure (BP), and oxygenation (SpO 2 ) alarms as quickly with vibrotactile displays as with a graphical monitor plus auditory alarms, suggesting that vibrotactile displays could be used to remove unwanted sound from clinical environments without risking less effective detection of patient deterioration.…”
Section: Vibrotactile Displays For Patient Monitoring In Healthcarementioning
confidence: 99%
“…However, an advantage for such displays seems to have been found by Burdick et al (2019). In recent work, Alirezaee et al (2020) demonstrated that nonclinician participants could detect heart rate (HR), blood pressure (BP), and oxygenation (SpO 2 ) alarms as quickly with vibrotactile displays as with a graphical monitor plus auditory alarms, suggesting that vibrotactile displays could be used to remove unwanted sound from clinical environments without risking less effective detection of patient deterioration.…”
Section: Vibrotactile Displays For Patient Monitoring In Healthcarementioning
confidence: 99%
“…There are many applications where the elements of the environment need to be taken into consideration when performing a task, such as in semi-autonomous vehicles [34], flight control systems [35] and healthcare devices for surgery [36,37]; this is particularly important for for autonomous agriculture machine operators [38]; visually impaired individuals [39][40][41]; and construction workers [42]. In all these cases, tactile memory could potentially make performing the task more efficient and safe.…”
Section: Introductionmentioning
confidence: 99%